(untitled) (Cadernos ESP, 2023)
Carry out an epidemiological survey of teenage pregnancy cases in the municipality of Quixeramobim-Ce. Descriptive, epidemiological and observational study. Held in 2022, with data from pregnant adolescents, aged between 10 and 19 years. Information extracted from the information website of the Ministry of Health (DATASUS) and the epidemiological surveillance of the municipality, with a temporal cut of the years 2018 and 2021. The year with the highest rate of teenage pregnancy was in 2018, with the lowest rate in 2020. Regarding the age group of these adolescents, those aged between 15 and 19 have a higher prevalence of pregnancy. There was a drop in the rate of teenage pregnancy. Although there was an increase in 2018, there was a decline in the rate between 2019 and 2020, growing again only in 2021.